Structural dynamics of melting and glass formation in a two-dimensional hybrid perovskite - Chumei Ye; Lauren N. McHugh; Pierre Florian; Ruohan Yu; Celia Castillo-Blas; Celia Chen; Arad Lang; Yuhang Dai; Jingwei Hou; David A. Keen; Siân E. Dutton; Thomas D. Bennett (Nature Communications)
Abstract Hybrid organic-inorganic perovskites (HOIPs) have garnered significant attention for their crystalline properties, yet recent findings reveal that they can also form liquid and glassy phases, offering an alternative platform for understanding non-crystalline materials. In this study, we present a detailed investigation into the structural dynamics of the melting and glass formation process of a two-dimensional (2D) HOIP, (S−(−)−1-(1−naphthyl)ethylammonium)2PbBr4. Compared to its crystalline counterpart, the glass exhibits superior mechanical properties, including higher Young’s modulus and hardness. Our structural studies reveal that the liquid and glass formed from the 2D HOIP exhibit network-forming behaviour, featuring limited short-range order within individual octahedra, partial retention of metal-halide-metal connectivity between neighbouring octahedra, and residual structural correlations mediated by organic cations. We then combine in situ variable-temperature X-ray total scattering experiments, terahertz far-infrared absorption spectroscopy and solid-state nuclear magnetic resonance techniques to study the melting mechanism and the nature of the HOIP liquid obtained. Our results deepen the understanding of the structural evolution and property relationships in HOIP glasses, providing a foundation for their potential applications in advanced phase-change material technologies.